Cyber-support: An analysis of online self-help forums (online self-help forums in bipolar disorder). (June 2013) - Bauer, Rita; Bauer, Michael; Spiessl, Hermann; Kagerbauer, Tanja
<x xml:space="preserve">Abstract</x> Background: The Internet is becoming increasingly important in psychiatry and psychotherapy. Aims: The objective of this study was to evaluate if and how online self-help forums are used by patients with bipolar disorders, their relatives and treating professionals. Methods: A total of 2400 postings in two online forums were analysed qualitatively and quantitatively. Results: "Disclosure", "friendship" and "online-group cohesion" were the main self-help mechanisms. The topics most discussed were "social network", "symptoms of the illness" and "medication". Factor analyses revealed three factors concerning self-help mechanisms: "group cohesion", "emotional support" and "exchange of information", as well as three factors concerning fields of interest: "illness-related aspects", "social aspects" and "financial and legal issues". Conclusion: We infer that the main interest in participating in online forums for patients with bipolar disorders and their relatives is to share emotions and to discuss their daily struggles with the illness. Our study also reveals that social networking is very important for patients coping with bipolar disorders. Psycho-educative programmes should focus on those aspects.